PENGARUH KOMPENSASI KERJA, MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR INSPEKTORAT KABUPATEN NIAS SELATAN - Laia, Elisabeth Mawasti; Fau, Samanoi Halowo (PARETO : Jurnal Riset Bisnis dan Manajemen, 2022)
The problem of this research is Storey Level officer contribution which is expressed in solving of duties becoming its responsibility relative lower. The target of this research is to know the influence of work compensation, work motivation and culture organizational to Employee Performance at Inspektorat Office Sub-Province of South Nias. This Type Research is quantitative. Subject in this research is an Employee at Inspektorat Office Sub-Province of South Nias. The result of this research indicate that the workers compensation, work motivation and culture organizational have effect positive and significant to Employee Performance proved with value of Fcount equal to 50,528 > value of Ftable equal to 3,31 and level of signifikan equal to 0,000 < 0,05. Thereby can be concluded that work compensation, work motivation and culture organisation to Employee Performance to officer performance at Inspektorat Office Sub-Province of South Nias. Raised by Suggestion researcher is shall apply work compensation, work motivation and culture organizational better and effectively to maintain and improve officer employee performance through indicators of work compensation, work motivation and culture organizations to increase good employee performance now and also in the future and expected by period to come more improved again in the effort reaching the target of organization.